Predictive and prognostic significance of tumour subtype, SSTR1‐5 and e‐cadherin expression in a well‐defined cohort of patients with acromegaly. Issue 5 (24th January 2021) - Soukup, Jiri; Hornychova, Helena; Manethova, Monika; Michalova, Kvetoslava; Michnova, Ludmila; Popovska, Lenka; Skarkova, Veronika; Cesak, Tomas; Netuka, David; Ryska, Ales; Cap, Jan; Hána, Václav; et al.
Abstract: In somatotroph pituitary tumours, somatostatin analogue (SSA) therapy outcomes vary throughout the studies. We performed an analysis of cohort of patients with acromegaly from the Czech registry to identify new prognostic and predictive factors. Clinical data of patients were collected, and complex immunohistochemical assessment of tumour samples was performed (SSTR1‐5, dopamine D2 receptor, E‐cadherin, AIP). The study included 110 patients. In 31, SSA treatment outcome was evaluated. Sparsely granulated tumours (SGST) differed from the other subtypes in expression of SSTR2A, SSTR3, SSTR5 and E‐cadherin and occurred more often in young. No other clinical differences were observed. Trouillas grading system showed association with age, tumour size and SSTR2A expression. Factors significantly associated with SSA treatment outcome included age, IGF1 levels, tumour size and expression of E‐cadherin and SSTR2A. In the group of SGST, poor SSA response was observed in younger patients with larger tumours, lower levels of SSTR2A and higher Ki67. We observed no relationship with expression of other proteins including AIP. No predictive value of E‐cadherin was observed when tumour subtype was considered. Multiple additional factors apart from SSTR2A expression can predict treatment outcome in patients with acromegaly.